Synthesis and Crystal Structure of 2,2'-[Ethylenedioxybis(nitrilomethylidyne)]dinaphthalene - Sun, Yin-Xia; Lan, Qing-Ying; Meng, Wei-Sheng; He, Xue-Ni (Asian Journal of Chemistry, 2013)
A novel Schiff-base bisoxime compound, with the molecular formula C24H20N2O2, has been synthesized and characterized by elemental analysis, IR, 1H NMR and X-ray single-crystal diffraction. Structural analysis revealed that 2,2'-[ethylenedioxybis(nitrilomethylidyne)]dinaphthalene lies across a crystallographic inversion centre (symmetry code: -x, -y, -z) and adopts an E configuration with respect to the azomethine C=N bond. Within the molecule, the naphthalene units are parallel, but extend in opposite directions from the dimethylene bridge. In the crystal structure, weak intermolecular C-H···N hydrogen bonds and C-H···p stacking interactions link molecules into infinite three-dimensional supramolecular network structure.